The Asian factor: Methodological barriers to the study of Asian gangs and organized crime - Song, John Huey-Long (American journal of criminal justice, 1996)
This paper examines methodological barriers that confront the study of Asian criminal gangs and organized crime. Researchers need to address definitional issues, appreciate the pluralistic nature of Asian communities, incorporate region as a unit of analysis, enhance the reliability of interviewees’ responses, and recognize the impact of news media on the public perception of Asian crime. A research agenda is offered to deal with these issues in future research endeavors.